Digital narratives: a study of the Arcade Fire interactive music videos - Barboza, Elisa Maria Rodrigues (2015)
Initially seen as an audiovisual product made mainly for television, the music video, in recent years, has been expanding itself and gaining strength in the virtual environment. The possibility of easy and quick access through websites such as Vimeo and YouTube, besides the greater freedom these sites offer in comparison to the schedules of television channels, was only the beginning of the process of this format’s creative development. Its embracing of the technological changes culminates with the appearance of interactive music videos that strengthen investments made in experiences of digital narratives. In this context, one of the bands that stands out is Arcade Fire, whose trajectory already counts with four interactive audiovisual projects, namely Neon Bible (Vincent Morisset, 2007), Sprawl II (Vincent Morisset, 2010), The Wilderness Dowtown (Chris Milk, 2010) and Just a Reflektor (Vincent Morisset, 2013).